2020
DOI: 10.1002/acp.3744
|View full text |Cite
|
Sign up to set email alerts
|

How old was he? Disguises, age, and race impact upon age estimation accuracy

Abstract: Summary There are many situations in which a person must accurately estimate a stranger's age. For example, a salesperson must accurately estimate the age of a stranger who wishes to purchase age‐restricted goods. Information from a stranger's eyes and hair can indicate their likely age. Here, two experiments examined whether adult participants' accuracy when estimating strangers' ages is reduced when the strangers' eyes are disguised by sunglasses and/or hair is disguised by a hat. The strangers' age and race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 48 publications
(140 reference statements)
3
8
0
Order By: Relevance
“…Studies similar to ours have also shown estimates of undisguised young adults' ages are inaccurate by an average that is close to 5 years (e.g. Short et al, 2019;Thorley, 2021;Voelkle et al, 2012). Additionally, we replicated Thorley's (2021) past result showing participants continue overestimating young adults' ages when they are wearing sunglasses.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Studies similar to ours have also shown estimates of undisguised young adults' ages are inaccurate by an average that is close to 5 years (e.g. Short et al, 2019;Thorley, 2021;Voelkle et al, 2012). Additionally, we replicated Thorley's (2021) past result showing participants continue overestimating young adults' ages when they are wearing sunglasses.…”
Section: Discussionsupporting
confidence: 86%
“…All faces in this study belonged to young adults as we wished to test the replicability of Thorley's (2021) previous finding showing estimates of their ages are no less accurate when they are pictured wearing sunglasses. His finding could be considered surprising, given that the eye region contains important information about a face's age.…”
Section: Aims and Hypothesesmentioning
confidence: 94%
See 1 more Smart Citation
“…Other group characteristics may also account for some of the variance recorded in the present study, namely gender and ethnicity of stimulus and participants. Although these characteristics have not been extensively documented, existing findings suggest that Caucasian participants perform better when evaluating Caucasian faces (Dehon & Brédart, 2001; Thorley, 2021), but this own‐ethnicity bias does not persist for African participants (Dehon & Brédart, 2001). Few studies have examined own‐gender bias in age estimation from faces, and those which have did not find evidence to support this (Dehon & Brédart, 2001; Voelkle et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Only a small set of studies have examined the effect of obscuring different facial features on age perception. In those studies, obscuring head shape and hair did not decrease accuracy (George & Hole, 1995), but obscuring the eye region led to a greater reduction in accuracy compared to disguising the hair and forehead or no disguise at all (Thorley, 2021). Furthermore, a recent eye‐tracking study suggests that the central triangle (collectively eyes, nose, and mouth) may be important for age estimation (Liao et al, 2020).…”
Section: Introductionmentioning
confidence: 96%